Implementasi Raspberry Pi 3 Sebagai Wireless Access Point Pada STIPER Sriwigama Palembang - Rahmat Novrianda Dasmen (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
STIPER Sriwigama Palembang is one of the agricultural science college located in Palembang City. STIPER Sriwigama Palembang has a computer network that utilizes wireless transmission media. Therefore, one of the most needed devices is AP (Access Point). Currently, STIPER Sriwigama Palembang only has 2 Access Point so that the internet network can not be spread to the entire environment of STIPER Sriwigama Palembang. With these problems, in this research will be designed WAP (Wireless Access Point) by utilizing Raspberry Pi 3 Model B owned by STIPER Sriwigama Palembang. Raspberry Pi 3 Model B is a mini computer that is about the size of a credit card equipped with SD card which is where the installation of Operating System and data storage managed on Raspberry Pi 3. Building a Wireless Access Point can be done by doing some configuration stages to Raspberry Pi 3 Model B which has been installed by Raspbian Operating System. With the construction of WAP utilize Raspberry Pi 3, then the internet network will be spread throughout the environment of STIPER Sriwigama Palembang by using wireless transmission media.